Associação de pré-diabetes com marcadores precoces de lesão cardiovascular - Firmino, Stella Maris (Universidade Federal de São Carlos, 2021)
Introduction: Diabetes mellitus type 2 (DM2) is responsible for about 90% of diabetes cases and its mortality is associated with micro and macrovascular complications. Individuals who are at a higher risk of developing DM2 are called prediabetics (PD). It is estimated that approximately 25% of individuals with PD will develop DM2 in three to five years. It is not yet clear in the literature how is the cardiovascular function of these patients. It is believed that there are early markers of cardiac and endothelial dysfunction in this population and that they may be associated with impaired quality of life. Objectives: To assess the presence of early markers of impairment in endothelial and cardiovascular function in PD patients compared to normoglycemic individuals and to investigate if there is an association of these markers with worsening of the quality of life. Methods: Cross-sectional clinical study with the composition of two groups: Prediabetics (PD): who met the criteria for PD and are not on hypoglycemic medication; and Normoglycemic Control (NG): who do not meet the criteria for DM and PD. Patients in both groups had no known cardiovascular disease. They underwent clinical and physical evaluation, echocardiogram, evaluation of carotid intima-media thickness (CIMT), evaluation of arterial stiffness (AR) through pulse wave velocity (PWV), SF-36 quality of life questionnaire, and sedentary lifestyle IPAQ questionnaire. Statistical analysis: comparison of groups using the Chi-square test for categorical variables, T Student test for variables with normal distribution and Man-Whitney for variables with non-normal distribution. Associations between variables in the same group were assessed by linear regression. Results: The groups were homogeneous in relation to baseline and clinical variables. In the PD group, a greater association with dyslipidemia (p<0.001) was observed, in addition to early signs of diastolic dysfunction assessed by the E wave velocity of the Mitral flow E (E (cm/s): NG 84.08 ± 13.56 vs PD 77.70 ± 11.82, p = 0.03) and greater RA (VOP (m/s): NG 7.16 ± 1.54 vs PD 7.92 ± 1.75, p = 0.04). In the linear regression model, the presence of impaired glucose tolerance was an independent factor associated with the E wave of the Mitral flow, even adjusting for confounding variables (p = 0.02). There was more prevalence of right ventricle diastolic dysfunction, regarding to E/A ratio of Tricuspid Inflow (p = 0.03) and E’ Tricuspid of Tissue Doppler (p = 0.04). The PD group also showed greater impairment in quality of life in functional capacity (p = 0.03), pain (p = 0.03), vitality (p = 0.03) dominoes and also a higher degree of sedentary lifestyle by the IPAQ score (p = 0.006). Glucose intolerance was associated with a higher degree of physical inactivity. Conclusion: PD individuals, compared to NG patients of similar age and sex, already have early markers of cardiac and endothelial dysfunction, in addition to greater impairment in quality of life. Decreased glucose tolerance, despite the association with other risk factors, such as dyslipidemia and physical inactivity, is an independent factor associated with thereductio of E mitral wave velocity.
Association of prediabetes with early markers of cardiovascular injury
Keywords: Disfunção cardiovascular; Disfunção endotelial; Pré-diabetes; Cardiovascular dysfunction; Endothelial dysfunction; Prediabetics; CIENCIAS DA SAUDE::MEDICINA; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA::CARDIOLOGIA